Transformasi Ritual Mahapuja Sebagai Adaptasi Budaya Dalam Komunitas Buddhis Tamil Sumatera Utara - Winja Kumari; Ida Bagus Gede Yudha Triguna; Putu Sarjana; Panir Selwen (Jayapangus Press, 2026)
This study examines cultural interrelation in transforming Buddhist teachings within Mahapuja practice at Tamil Buddhist temples in North Sumatra as an existential response by the diaspora community to maintain identity amidst a multicultural society. It analyzes dynamics of cultural linkage, mechanisms of doctrinal transformation through ritual, and implications for community spirituality and identity. Using a qualitative phenomenological-ethnographic approach (2023-2025), the study involved eight Tamil temples in Medan through interviews with 31 key informants, participatory observation, and document analysis. Findings reveal that the interrelation between Buddhist teachings and Tamil culture in Mahapuja is not passive acculturation, but active syncretism as an existential strategy. Transformation occurs through four mechanisms: Tamil language integration as pedagogical medium, multisensory ritual as holistic education, hermeneutical reinterpretation of Hindu-Tamil elements, and digital innovation. Mahapuja functions dually as a medium for spiritual transformation connecting existential awareness (Das Sein) with moral commitment (Das Sollen), and as an identity preservation strategy through negotiated authenticity. Panditas play a central role as hermeneutic agents bridging generations to make abstract concepts existentially accessible. This study concludes that Mahapuja represents living vernacular Buddhism, where sustainability of Buddhist teachings is strengthened through creative dialogue between universal doctrine and Tamil cultural roots. Ritual authenticity is not measured by textual conformity to original tradition, but by its capacity to remain meaningful in the community's spiritual life. The dual Buddhist-Tamil identity forms harmoniously without internal conflict. Theoretical findings enrich concepts of negotiated authenticity and vernacular Buddhism in lived religion studies, while practical findings offer an inclusive religious education model for minority religious communities maintaining tradition sustainability amidst global modernity.